Hubungan Dukungan Keluarga Dengan Kepatuhan Penderita Kusta Dalam Menjalani Pengobatan di Wilayah Kerja Puskesmas Sine, Kabupaten Ngawi - Yudha Fika Diliyana (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Family support is needed by leprosy patients in treatment. Noncompliance treatment can trigger a relapse and prolong the duration of treatment. This study aims to determine the relationship between family support compliance in the treatment of leprosy patients in health centers Sine working area. The study design used is Analytical sectional. By using purposive sampling technique as much as 30 respondents participated in the study. The instrument used in this study were (1) questionnaire respondent characteristics, (2) questionnaires family support, (3) calculate the rest of the drug in patients with leprosy. Cronbach alpha reliability test on the questionnaire of family support r = 0.752. The results showed that the majority of leprosy patients gain positive support of the family as much as 18 (60.0%), while a small portion of negative family support gained as much as 12 leprosy patients (40.0%). Most of the leprosy patients adherence to the treatment of leprosy were 27 (90.0%), while non-adherent to run as much as 3 treatment of leprosy patients (10,0%). Relationship with the family support treatment adherence leprosy patients based on the results of the chi squared x2 count